PENCEGAHAN PENULARAN PENYAKIT SKABIES DAN PRILAKU HIDUP BERSIH SEHAT (PHBS) DI PONDOK PESANTREN AL- FALAH KOTA PADANG - Rosmaini, Rosmaini; Yuliza Birman; Suharni, Suharni; Andika Calfriarsada; Maharani, Siti assyifa; Alfarel, Ibnu Khalid (CV. Alina, 2025)
Scabies is a contagious skin infection caused by the mite Sarcoptes scabiei, characterized by intense itching and the appearance of a rash. It most commonly affects children and the elderly, with prevalence among children ranging from 5% to 50%. Scabies spreads easily through both direct and indirect contact. Practicing Clean and Healthy Living Behavior (CHLB) is essential in preventing transmission. Health education through outreach programs plays a crucial role in increasing public knowledge and awareness about disease prevention. The Faculty of Medicine at Baiturrahmah University conducted a community service activity as part of the Medical Baiturrahmah Social in Action (MBSA) event, which included education on scabies transmission prevention and the importance of CHLB to help curb the spread of the disease and raise awareness about the importance of hygiene. This activity is expected to reduce the incidence of scabies and inspire the community to incorporate CHLB into their daily.